Effects of two kinds of Kampo‐hozai, ninjinyoeito and kamikihito, on mental disorder‐like behaviors in senescence‐accelerated mouse‐prone 8 mice. Issue 2 (15th June 2021) - Hirata, Marika; Taniguchi, Chise; Watanabe, Takuya; Horikawa, Toru; Akizuki, Yufuko; Kubota, Kaori; Katsurabayashi, Shutaro; Iwasaki, Katsunori
ABSTRACT: Aim: Ninjinyoeito (NYT) and kamikihito (KKT) are two types of a group of Japanese herbal medicines called 'Kampo‐hozai', which can improve depleted mental and physical energy in a variety of patients. NYT and KKT are therefore also expected to improve the symptoms of aging. However, evidence of the therapeutic effects of NYT and KKT on age‐related mental disorders in basic research remains scarce. The present study examined the effects of NYT and KKT on mental disorder‐like behaviors in senescence‐accelerated mouse‐prone 8 (SAMP8) mice, a model of accelerated aging. Methods: SAMP8 mice were orally administered NYT or KKT (300 or 1000 mg/kg/d) starting from 12 weeks of age. A splash test was conducted at 21 weeks of age. An open‐field test was conducted at 20 and 33–34 weeks of age. Results: Treatment with NYT, but not KKT, increased the grooming time of SAMP8 mice in the splash test at 21 weeks of age, suggesting that NYT ameliorates apathy‐like behavior. In contrast, treatment with KKT, but not NYT, increased the time spent by SAMP8 mice in the inner zone of the open‐field test at 33–34 weeks of age, suggesting that KKT ameliorates anxiety‐like behavior. Conclusion: NYT and KKT may be useful for treating apathy and anxiety, respectively, in older individuals.